Analysis and Optimization of Inventory Control in Supporting Efficient and Innovative Industrial Development - Juliardin; Rizqullah Salman; Muhammad Iqbal; Munadi Agri Saswan (Masterpiece, 2026)
This study analyzes and optimizes inventory control practices to support the development of efficient and innovative industrial operations through a community service program conducted at PT Dirgaputra Ekapratama, Samarinda Branch. The primary objective is to enhance inventory management control and improve warehouse staff competencies. The study adopts an educational and participatory approach, utilizing semi-structured interviews, direct observation, document analysis, and on-site mentoring to identify operational issues and implement practical solutions. Key problems identified include low frequency of stock opname, absence of continuous recording systems, reliance on manual and non-standardized documentation, and inefficiencies in item handling. Three integrated solutions were introduced: increasing stock opname frequency to twice weekly, implementing standardized stock cards for real-time recording, and introducing barcode technology to improve identification accuracy and operational speed. The results indicate a significant improvement in inventory data accuracy, enhanced recording efficiency, and stronger staff discipline in following procedures. Additionally, the initiative successfully fostered organizational commitment toward adopting technology-based warehouse management systems. Although full implementation of stock cards and barcode systems requires further approval from headquarters, the pilot implementation demonstrated feasibility and effectiveness. The findings highlight that structured procedures, combined with gradual technological adoption and managerial commitment, play a critical role in strengthening internal control systems. This study contributes to practical inventory management improvements and supports sustainable industrial development aligned with efficiency and innovation principles